2015
DOI: 10.1002/eji.201545537
|View full text |Cite
|
Sign up to set email alerts
|

TSLP production by dendritic cells is modulated by IL‐1β and components of the endoplasmic reticulum stress response

Abstract: Thymic stromal lymphopoietin (TSLP) produced by epithelial cells acts on dendritic cells (DCs) to drive differentiation of TH2‐cells, and is therefore important in allergic disease pathogenesis. However, DCs themselves make significant amounts of TSLP in response to microbial products, but little is known about the key downstream signals that induce and modulate this TSLP secretion from human DCs. We show that human monocyte derived DC (mDC) secretion of TSLP in response to Candida albicans and β‐glucans requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 46 publications
2
47
0
Order By: Relevance
“…Previous work has highlighted the importance of IL-1β secretion in orchestrating dectin-1-mediated immune responses (12, 16, 23). Therefore, we examined whether the amount of IL-1β stimulated by β-glucan particles of different sizes is critical in determining the amounts of other cytokines produced.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has highlighted the importance of IL-1β secretion in orchestrating dectin-1-mediated immune responses (12, 16, 23). Therefore, we examined whether the amount of IL-1β stimulated by β-glucan particles of different sizes is critical in determining the amounts of other cytokines produced.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, TSLP was shown to prime DCs for adaptive Th2 responses and this role was thought to be primarily responsible for downstream type 2 inflammation driven by TSLP [ 26 ]. In addition to responding to TSLP, a recent human study showed that dendritic cells exposed to fungal allergen are also a potent source of TSLP [ 31 ]. Furthermore, recent studies have identified basophils and mast cells as additional sources of TSLP [ 32 ].…”
Section: Thymic Stromal Lymphopoietin (Tslp)mentioning
confidence: 99%
“…In mice, intratumoral application of Curdlan was found to reprogram infiltrating DCs to become resistant to cancer‐derived thymic stromal lymphopoietin (TSLP), thus favoring the generation of beneficial Th1‐based immune responses . In contrast, during microbial infections, Dectin‐1 activation induced TSLP release by DCs, thus promoting Th2‐biased immunity . However, the importance of DC‐intrinsic TSLP production in the context of tumor immunity remains to be determined.…”
Section: Resultsmentioning
confidence: 99%